Strategy for immunological analysis of pro-inflammatory cytokine marker studies with chronic hepatitis B virus in Southwestern region of Saudi Arabia - Amal F. Alshammary; Raed Farzan; Sarah F. Alsobaie; Arwa A. Alageel; Imran Ali Khan (Elsevier, 2023)
Background: Hepatitis B Virus (HBV) is one of the leading causes of infectious disease in the global population, and its prevalence has been increasing globally. Human HBV infection is complex, involving both innate and adaptive immune systems. Cytokines play a role in both physiologic and pathologic processes in the liver. This study was designed to screen serum levels using an enzyme linked immunosorbent assay (ELISA) and genetic variants in the TNF-α and IL6 genes using polymerase chain reactions (PCR). The aim of this study was to screen the serum levels and genotype levels with TNF-α (C-308 T/G-308A) and IL-6 (G-174 C) genes in HBV patients and control subjects. Methods: In this study, we have selected 50 HBV patients and 40 control subjects from Saudi Population. Patient serum samples was used for measuring the serum levels and PCR analysis using RFLP analysis. Prior to this, HBV patients were confirmed with PCR analysis followed by Sanger sequencing analysis. Results: The current study results confirmed positive association in serum levels (p < 0.05) and negative association with both genotype and allele frequencies in TNF-α (C-308 T) and IL-6 (G-174 C) genes among HBV patients and controls (p > 0.05). Positive associations between blood levels of TNF-α and IL-6 were confirmed, while negative associations were found between PCR investigations involving the TNF-α (G-308A) and IL-6 (G-174 C) genes with the HBV prevalence in the Saudi population. Conclusion: This study confirmed serum levels are strongly associated with HBV patients in the Saudi population. However, PCR studies showed the negative association with the couple of variants selected for this study.